Pengaruh penerapan kurikulum merdeka terhadap prestasi belajar siswa - Dhea Amelia; Muhammad Ripai; Taufik Kusuma Panjaitan; Inayah Hanum Lubis; Safinatul Hasanah Harahap (Indonesian language and literature education program Majapahit Islamic University, 2024)
The curriculum is a set of plans and arrangements regarding the objectives of the content of learning materials and the methods used as learning guidelines. The Merdeka curriculum has been implemented since the outbreak of Covid-19 which occurred in 2020, which had a negative impact on the learning and education process in Indonesia. The Independent Curriculum has become a major concern in the world of education today. The research method used in this research is a qualitative research method which can help to gain an in-depth understanding of the effect of implementing the Merdeka curriculum on increasing student learning achievement. The main aim of this research is to evaluate the effect of implementing the Merdeka curriculum on increasing student learning achievement. The results obtained through this research are that the implementation of the Independent curriculum has a positive influence on increasing student learning achievement with a number of advantages from implementing the Independent curriculum. Thus, this research provides a basis for developing a more effective and relevant curriculum to improve student learning achievement in the future.